Pengaruh Parent Involvement dan Academic Self-Concept Terhadap School Engagement Dalam Situasi Pandemi Covid-19 Pada Siswa SMK “X” Di Kota Bandung - Kusumapratiwi, Ciptaning Putri Kukuh; Savitri, Jane; Rohinsa, Meiliani (Journal of Research and Measurement in Psychology: JPPP, 2023)
The purpose of this study was to see the influence of parent involvement and academic self-concept on school engagement among students at SMK "X" Bandung. This research was conducted to look at parent involvement and academic self-concept on school engagement in class X – XII students at SMKN "X" Bandung City. This study refers to the theory of parent involvement, academic self-concept as the independent variable, and school engagement as the dependent variable. The researcher gave parent involvement, academic self-concept, and school engagement questionnaires to the students of SMK "X" Bandung. The research methodology is multiple regression quantitative method with a total sample of 368 students taken randomly at each grade level. Data processing uses the SPSS 22 technique. The results show that there is an effect of parent involvement on school engagement, there is an influence of academic self-concept on school engagement, and there is an influence of academic self-concept and parent involvement simultaneously on school engagement in SMK students. X Bandung. The researcher suggests the next researcher to conduct research on high school (non-vocational high school), to see whether the same trend can occur in other high school environments, and to conduct research by adding other variables so that the effects of the various variables can be mapped.